The Influence of Psychological Factors on Ethical Decision Making in Islamic Educational Institutions at Assalaam Plus High School - Ahsyaf Muzakki; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article was written to examine the influence of psychological factors on ethical decision-making in Islamic educational institutions. The research method used in writing this article is a qualitative method with a descriptive approach. Data collection techniques were carried out through: first, in-depth interviews; second, participant observation and third, documentation. Meanwhile, the data collected through the three techniques above were then checked for validity by checking credibility. Research results The influence of psychological factors on ethical decision-making at SMA Plus Assalaam The module project